Is This What an Environmentalist Looks Like? - Bose, Pablo (UnderCurrents: Journal of Critical Environmental Studies, 2002)
Somewhere on the streets of Seattle, on a brightwinters day in 1999, someone called me an environmentalist. I still haven’t quite recovered from the shock.